Cellulose microfibres from traditional rice straw: Physicochemical properties and analytical characterization. (2021) - Ratnakumar, A.; Samarasekara, A.M.P.B.; Amarasinghe, D.A.S.; Karunanayake, L.
Abstract: In this work, cellulose microfibres (CMF) were isolated from rice straw of traditional rice varieties in two distinct stages. Initially, samples were treated with a sequence of chemical processes and the obtained cellulose fibres were then mechanically separated into cellulose microfibres using ultrasonic process. FTIR analysis confirmed that the chemical composition of CMF was mainly cellulose where conspicuous peaks of hemicelluloses and lignin were effectively removed during the chemical treatments. From the thermal analysis it was evident that the ultrasonic treatment had little effect on the thermal decomposition of the CMF. The findings of this study will add value to the commercially under-utilized waste rice straw and also accentuate sustainable transition to a bioeconomy in paddy cultivating countries.